Modelling and simulation of mitral valve for transapical repair applications - Gaidulis, Gediminas; Selmi, Matteo; Zakarkaitė, Diana; Aidietis, Audrius; Kačianauskas, Rimantas (Nonlinear Analysis: Modelling and Control, 2019)
Development and application of the numerical model for the simulation of human heart mitral valve (MV) transapical repair is presented. Transapical repair with neochordae implantation is a novel surgical technique allowing beating-heart correction of mitral regurgitation caused by chordae tendineae rupture through a minimally-invasive approach. In the present study, the structural finite element model of the MV decoupled from the blood flow is considered. It comprises two leaflets and chordae tendineae described by nonlinear material model. Geometry of the model and kinematic boundary conditions for fixed points of MV annulus, papillary muscles, and left ventricle apex are defined by patient-specific data. Decoupled behavior of blood is specified by the time-dependent physiologic transvalvular pressure.Personalized computational modelling strategy is applied to perform virtual transapical MV repair by positioning neochordae following the real-life surgery procedure executed by surgeons. A transient analysis in time frame between end-diastole and peak systole is conducted to evaluate post-repair MV function. Computational MV simulation and modelling results provide quantitative information about the neochordae contribution to the MV function improvement and present practical value for the surgical planning of transapical MV repair.
Keywords: mitral valve; prolapse; mitral regurgitation; neochordae; transapical; explicit finite element analysis